Ekoteologi : Memahami Kehadiran Allah Dalam Bencana Alam Ditunjau dari Perspektif Perjanjian Lama (International Forum of Researchers and Lecturers, 2024)
In this paper, we want to present the development of several previous writings and then make them into new topics related to God's presence in natural disasters by looking at them from the perspective of the Old Testament. There are so many responses from religious people, especially in Christianity, about God's presence in a disaster or natural disaster. There are those who think that the cause of disasters is humans themselves, there are also those who assume that disasters arise because God wants to give a warning or punishment to humans. Therefore, this article will describe God's presence in a disaster in general.